Quantum dot intermediate band solar cell based on II-type energy band structure and preparation method of quantum dot intermediate band solar cell

By using a quantum dot technology with II -type energy structure with a solar cell in the middle, using CDTE quantum dot and MAPBBR3 perovskite composition to solve the problem of low efficiency of the existing intermediate with solar cells in the middle, realize a wider range Photon absorption and higher battery performance.

CN119384141APending Publication Date: 2025-01-28HEBEI UNIVERSITY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411963870.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The actual efficiency of existing intermediate-band solar cells is much lower than their theoretical efficiency, and the band gap of perovskite materials is not suitable for the preparation of intermediate-band solar cells.

Method used

The middle of the quantum dot of the II -based energy -based structure is used with a solar cell, and the II energy type can be composed of the II energy type by using CDTE quantum dot and MapbBR3 perovskite, forming a range that can be widening the solar spectrum.

Benefits of technology

A two -step photon absorption with a solar cell in the middle has been realized, the life of the load and the opening voltage is improved, and the use of the solar spectrum is widened.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119384141A_ABST
    Figure CN119384141A_ABST
Patent Text Reader

Abstract

The invention provides a quantum dot intermediate band solar cell based on an II-type energy band structure and a preparation method of the quantum dot intermediate band solar cell. The intermediate band solar cell structure provided by the invention comprises an FTO conductive substrate, a TiO2 compact layer, a TiO2 mesoporous layer, a light absorption layer and a carbon electrode. The intermediate zone solar cell is manufactured by the following steps of: sequentially spin-coating and depositing the TiO2 compact layer and the TiO2 mesoporous layer on the FTO conductive substrate; the preparation method comprises the following steps: preparing CdTe quantum dots of an oleic acid (OA) ligand by a thermal injection method, carrying out ligand exchange, centrifuging the CdTe quantum dots after modification of the ligand, dispersing the CdTe quantum dots in N-methylformamide (NMF), mixing the CdTe quantum dots with an NMF solution of MAPbBr3, and carrying out spin coating to prepare a light absorption layer; and then blade-coating a carbon electrode on the light absorption layer by using a blade-coating method. The CdTe quantum dots and the MAPbBr3 perovskite are used for forming an II-type energy band structure, so that the service life of a carrier is prolonged, and the open-circuit voltage is maintained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of perovskite solar cells, in particular to a quantum dot intermediate band solar cell based on a type II energy band structure and a preparation method thereof. Background Art

[0002] Traditional resources such as coal, oil, and natural gas are non-renewable and can easily cause damage to the ecological environment. Clean solar energy has the advantages of being renewable, widely distributed, and easily accessible. The use of solar energy is considered to be the best way to replace traditional energy materials, and solar cells are the most direct way to use solar energy. With the continuous development of solar cell materials and technologies, the efficiency of single-junction solar cells is gradually approaching the Shockley-Queisser (SQ) efficiency limit. The theoretical efficiency of intermediate-band solar cells greatly exceeds the SQ efficiency limit, reaching 63.1% under full concentration conditions, and has therefore become one of the topics of concern.

[0003] In 1997, Luque, Martí and others proposed a physical model of intermediate-band solar cells through theoretical calculations. In 2000, Luque and others discussed the possibility of manufacturing intermediate-band solar cells through quantum dot technology, and proposed that quantum dot intermediate-band solar cells need to have three independent quasi-Fermi levels and keep the electrons half-filled after the intermediate band is formed. In 2015, Márton and others proposed through first-principles calculations that colloidal quantum dots (CNPs) are a reliable platform for realizing intermediate-band solar cells and are the only material suitable for "full spectrum enhancement" devices. In 2019, Hiroji Hosokawa and others prepared intermediate-band solar cells based on colloidal quantum dots for the first time by doping PbS quantum dots with wide-band gap material MAPbBr3, and confirmed that the prepared intermediate-band solar cells exhibit two-step photon absorption at room temperature. However, its band structure is a type I band structure, and the device shows a significant drop in open-circuit voltage. In 2023, G. Ribeiro et al. proposed a PbS / MAPbI3 composite film and optoelectronic device containing high-density embedded PbS based on a solution wet method, which achieved a sub-bandgap optoelectronic response based on the intermediate band. However, there is a problem that the bandgap of the selected perovskite material is not suitable for the preparation of intermediate band solar cells.

[0004] At present, the development of intermediate band solar cells is still in its early stages, and its actual efficiency is far lower than its theoretical efficiency. Therefore, it is of great significance to find materials with reasonable energy band structures and to regulate the preparation methods of intermediate band solar cells. Summary of the invention

[0005] The purpose of the present invention is to provide a quantum dot intermediate band solar cell based on type II band structure and a preparation method thereof. The present invention is based on CdTe quantum dots and MAPbBr3 perovskite to form a type II band structure, and obtains a wider photon absorption band through the intermediate energy band, thereby broadening the utilization range of the solar spectrum.

[0006] The present invention is achieved in that: The device structure of the quantum dot intermediate band solar cell based on type II energy band structure provided by the present invention comprises: an FTO conductive substrate; a TiO2 dense layer formed on the FTO conductive substrate; a TiO2 mesoporous layer formed on the TiO2 dense layer; a light absorption layer formed in the TiO2 mesoporous layer; and a carbon electrode formed on the light absorption layer. The light absorption layer is prepared by spin coating a light absorption layer precursor solution formed by CdTe quantum dots and MAPbBr3 perovskite, and the CdTe quantum dots are obtained by first forming an organic long-chain ligand on the surface of the quantum dots and then replacing the organic long-chain ligand with a short-chain ligand.

[0007] In the above scheme, the FTO conductive substrate is used for depositing thin films and scraping negative electrodes; scraping negative electrodes on FTO conductive substrates is a common practice in existing processes. For example, a high-temperature tape can be used to cover a portion of the surface on the FTO conductive substrate, and the high-temperature tape can be torn off when the positive electrode is prepared later, so that the positive electrode and the negative electrode are formed together. The TiO2 dense layer is used to receive photogenerated electrons and transmit them to the negative electrode; the TiO2 mesoporous layer is used to increase the contact area between the light absorbing material and the mesoporous TiO2, and optimize light scattering and transmittance; the light absorbing layer is used to absorb photons and convert them into electron-hole pairs; the carbon electrode is used to transmit holes and conduct electricity.

[0008] In the above scheme, preferably, the molar mass concentration of CdTe quantum dots in the light absorption layer precursor solution is 10% to 30%.

[0009] In the above scheme, preferably, the organic long-chain ligand is oleic acid, stearic acid, octadecylphosphonic acid, tetradecylphosphonic acid, oleylamine, octylamine or tributylphosphine; the short-chain ligand is methylammonium bromide, lead bromide, methylamine lead bromide, methylammonium iodide, lead iodide, methylamine lead iodide, sodium sulfide, sodium chloride or ammonium chloride.

[0010] The preparation method of quantum dot intermediate band solar energy based on type II energy band structure provided by the present invention includes: preparing CdTe quantum dots with organic long chain (such as oleic acid) ligands by hot injection method; exchanging ligands of the prepared CdTe quantum dots by solution phase transfer method to convert them into short chain (such as methyl ammonium bromide) quantum dots, and dispersing them with polar solvents; mixing CdTe quantum dot dispersion with MAPbBr3 perovskite precursor liquid to prepare light absorption layer precursor liquid. And depositing TiO2 dense layer by spin coating method, depositing on FTO conductive substrate; depositing TiO2 mesoporous layer by spin coating method, depositing on TiO2 dense layer; depositing light absorption layer by spin coating method, depositing in TiO2 mesoporous layer; scraping a layer of carbon electrode by scraping method, forming on light absorption layer.

[0011] Specifically, the method for preparing a quantum dot intermediate band solar cell based on a type II energy band structure in the present invention comprises the following steps: S1. Dissolve tellurium powder in tributylphosphine, heat under nitrogen environment, and then add octadecene to obtain Te-TBP precursor solution; S2, mixing cadmium oxide, an organic compound and octadecene, passing nitrogen gas and heating; and then adding the Te-TBP precursor solution in step S1 to the heated solution; S3, mixing the solution obtained in step S2 with acetone, centrifuging, drying, and then dispersing in n-hexane to obtain a n-hexane dispersion of CdTe quantum dots; the obtained CdTe quantum dots form organic long-chain ligands on their surfaces; S4, preparing a TiO2 mesoporous layer precursor solution: mixing titanium dioxide slurry with anhydrous ethanol, and stirring to prepare a TiO2 mesoporous layer precursor solution; S5. Prepare MAPbBr3 perovskite precursor solution: mix methyl ammonium bromide and lead bromide, add to N-methylformamide solution, and stir overnight to obtain MAPbBr3 perovskite precursor solution; S6. Prepare a TiO2 dense layer precursor solution: mix isopropyl titanate with anhydrous ethanol, and mix hydrochloric acid with anhydrous ethanol; in a glove box under a nitrogen environment, slowly drop the anhydrous ethanol solution containing hydrochloric acid into the anhydrous ethanol solution of isopropyl titanate using a pipette, stir, and then filter to obtain a TiO2 dense layer precursor solution; S7, cleaning of the FTO conductive substrate: soak the FTO conductive substrate in toluene, acetone, anhydrous ethanol, and deionized water in turn and perform ultrasonic cleaning respectively, blow dry with a nitrogen gun after cleaning, and then use a plasma cleaning machine to clean the surface of the FTO conductive substrate; S8, quantum dot ligand exchange: dissolving the short-chain ligand in N-methylformamide, taking the n-hexane dispersion of CdTe quantum dots obtained in step S3, and adding n-hexane to dilute; adding the diluted CdTe n-hexane dispersion to the N-methylformamide solution of the short-chain ligand, stirring, so that the organic long-chain ligand on the surface of the CdTe quantum dots is replaced by the short-chain ligand, thereby realizing ligand exchange; S9, preparation of a TiO2 dense layer: spin-coating the TiO2 dense layer precursor solution in step S6 on the FTO conductive substrate cleaned in step S7 to prepare a TiO2 dense layer; S10, preparation of TiO2 mesoporous layer: spin coating the TiO2 mesoporous layer precursor solution obtained in step S4 on the TiO2 dense layer obtained in step S9 to obtain a TiO2 mesoporous layer; S11, preparation of light absorption layer precursor solution: adding n-hexane to the ligand exchange solution obtained in step S8 for washing, taking out the N-methylformamide dispersion of quantum dots after washing, adding anhydrous ethanol for centrifugation, and redispersing it in N-methylformamide solution after centrifugation; mixing the redispersed N-methylformamide dispersion of quantum dots with the MAPbBr3 perovskite precursor solution in step S5, stirring, and obtaining a light absorption layer precursor solution; S12, preparation of a light absorbing layer: spin coating the light absorbing layer precursor solution obtained in step S11 on the TiO2 mesoporous layer obtained in step S10, and the light absorbing layer precursor solution is filled in the mesopores of the TiO2 mesoporous layer to form a light absorbing layer; S13. Preparation of carbon electrode: A carbon electrode is prepared by scraping on the light absorbing layer obtained in step S12.

[0012] In the above scheme, preferably, the molar mass concentration of CdTe quantum dots in the light absorption layer precursor solution obtained in step S11 is 10% to 30%.

[0013] In the above scheme, preferably, the process conditions for preparing the light absorbing layer in step S12 are: spin coating at 800 rpm for 10 s, then spin coating at 4000 rpm for 60 s, and annealing at 100° C. for 10 min after spin coating to obtain the light absorbing layer.

[0014] In the above scheme, preferably, the quantum dots usually contain organic compounds as surface ligands present around the quantum dots. The organic compounds in step S2 can be, for example, oleic acid, stearic acid, octadecylphosphonic acid, tetradecylphosphonic acid, oleylamine, octylamine, and tributylphosphine. The quantum dots need to undergo ligand exchange to replace the surface organic long-chain ligands with short-chain ligands. Specifically, the following short-chain ligands can be replaced: methylammonium bromide, lead bromide, methylamine lead bromide, methylammonium iodide, lead iodide, methylamine lead iodide, sodium sulfide, sodium chloride, and ammonium chloride. Preferably, CdTe quantum dots use oleic acid as the surface ligand, and undergo ligand exchange for ligand modification to replace the surface oleic acid (OA) with short-chain methylammonium bromide (MABr).

[0015] The quantum dots are colloidal quantum dots and can form an interlaced II band structure with MAPbBr3. In addition to CdTe quantum dots, the quantum dots can also be CdSe quantum dots, InP quantum dots, ZnTe quantum dots or ZnSe quantum dots. The quantum dots are usually synthesized in an organic phase. Dispersing the quantum dots in NMF solvent can improve the dispersibility of the quantum dots.

[0016] In the light absorption layer, a hole-confined type II band structure can be formed from the energy level position. The quantum dot band gap energy is lower than the perovskite compound band gap energy, and the quantum dot band gap energy is higher than 0.2eV.

[0017] The present invention has the following beneficial effects: (1) By utilizing the confined energy levels of quantum dots, an intermediate energy band is obtained when the wave functions of adjacent quantum dots overlap, so that the intermediate energy band solar cell exhibits two-step photon absorption, enabling the intermediate energy band solar cell to utilize long waves.

[0018] (2) The CdTe quantum dots used are new materials for the intermediate-band solar system, which can form a type II band structure with MAPbBr3 perovskite, which is beneficial to the improvement of carrier lifetime and the maintenance of open-circuit voltage.

[0019] (3) The perovskite host material used has a band gap of 2.3 eV, which is conducive to the formation of an intermediate band with a reasonable energy band structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a schematic structural diagram of the intermediate zone solar cell provided by the present invention.

[0021] Figure 2 Flow chart for preparing an intermediate zone solar cell for the present invention.

[0022] Figure 3It is a schematic diagram of the energy band structure principle of the light absorption layer of the intermediate band solar cell; wherein, (a) is the energy band structure of CdTe and MAPbBr3 in the light absorption layer of the intermediate band solar cell of the present invention, and (b) is the working principle of the intermediate band.

[0023] Figure 4 is a SEM image of the sample prepared in Example 1 of the present invention.

[0024] Figure 5 It is a comparison diagram of the light absorption spectra of the corresponding light absorption layers in the 400nm-2000nm band in Examples 1 to 3 of the present invention and Comparative Example 1.

[0025] Figure 6 This is a comparison chart of the external quantum efficiency (EQE) of the intermediate zone solar cells prepared in Examples 1 to 3 of the present invention and the MAPbBr3 perovskite solar cell prepared in Comparative Example 1 at 400nm-1500nm.

[0026] Figure 7 This is an IT curve spectrum of the photoelectric response of the intermediate zone solar cell prepared in Example 2 of the present invention when excited by an 830nm laser.

[0027] Figure 8 This is an IT curve spectrum of the photoelectric response of the intermediate zone solar cell prepared in Example 2 of the present invention when excited by a 1550nm laser. DETAILED DESCRIPTION

[0028] like Figure 1 As shown, the quantum dot intermediate band solar cell based on type II energy band structure provided by the present invention comprises: an FTO conductive substrate composed of glass and an FTO layer, a TiO2 dense layer arranged on the FTO conductive substrate, a TiO2 mesoporous layer arranged on the TiO2 dense layer, a light absorption layer formed in the TiO2 mesoporous layer; and a carbon electrode arranged on the light absorption layer. The light absorption layer is prepared by spin coating a light absorption layer precursor solution formed by CdTe quantum dots and MAPbBr3 perovskite.

[0029] The preparation method of the quantum dot intermediate band solar cell based on type II energy band structure in the present invention is described in detail below through specific embodiments.

[0030] Example 1 Combination Figure 2 In this embodiment, the preparation method of the quantum dot intermediate band solar cell based on the type II energy band structure is as follows: S1: Take 140 mg of tellurium powder and dissolve it in a rubber-stoppered vial containing 2.65 mL of tributylphosphine (TBP) in a glove box. Heat it at 140 °C under a nitrogen environment until the solution is light green. After observing that there are no obvious black tellurium powder particles in the vial, use a syringe to inject 3.16 mL of octadecene into the solution and continue heating at 140 °C to obtain a Te-TBP precursor solution.

[0031] S2: Take 280mg of cadmium oxide, 2.65mL of oleic acid (OA), and 38mL of octadecene, mix and add them into a four-necked flask, and add a small magnet into the flask. Then open the nitrogen valve, stir and ventilate the four-necked flask under nitrogen for 30 minutes, and after ventilation, heat it to 260℃. After observing that the solution changes from a reddish-brown suspension to a colorless and transparent solution, use a glass syringe to draw the Te-TBP precursor solution and quickly inject it into the four-necked flask. At this time, observe that the solution quickly turns brown. Then keep it warm at 240℃ for 90 minutes.

[0032] S3: After the solution in the four-necked flask is cooled to room temperature, take out the solution and mix it with acetone at a volume ratio of 1:8, and centrifuge at 10000rpm for 3min. Repeat the above centrifugation step 5 times. After completion, the obtained CdTe-OA quantum dots are dried in a drying oven at 80℃ for 2 hours. After drying, they are dispersed in 16mL of n-hexane and stored in a glove box.

[0033] S4: Preparation of TiO2 mesoporous layer precursor solution: Mix 150 mg of titanium dioxide slurry (18NR-T) with anhydrous ethanol in a mass ratio of 1:7, and stir overnight for use.

[0034] S5: Preparation of MAPbBr3 perovskite precursor solution: Mix 89.6 mg of methyl ammonium bromide (MABr) and 293.6 mg of lead bromide (PbBr2) and add them to 1 mL of N-methylformamide (NMF) solution, stir overnight for use.

[0035] S6: Prepare TiO2 dense layer precursor solution: Mix 140 μL of isopropyl titanate with 1 mL of anhydrous ethanol, and mix 27 μL of 1 mol / L hydrochloric acid with 1 mL of anhydrous ethanol. In a glove box with a nitrogen environment, slowly add the anhydrous ethanol solution containing hydrochloric acid to the anhydrous ethanol solution of isopropyl titanate using a pipette, and stir for 1 hour. After stirring, filter with a 0.13 μm filter for later use.

[0036] S7: Cleaning of FTO conductive substrate. Soak the FTO conductive substrate in toluene, acetone, anhydrous ethanol, and deionized water in turn and perform ultrasonic treatment for 20 minutes. After cleaning, use a nitrogen gun to blow dry, and then use a plasma cleaner to clean the surface of the FTO conductive substrate.

[0037] S8: Quantum dot ligand exchange. Take 0.112 mg of methyl ammonium bromide and dissolve it in 4 mL of NMF solution; take 1 mL of n-hexane dispersion of CdTe-OA quantum dots and add 3 mL of n-hexane to dilute. Add the diluted CdTe-OA n-hexane dispersion to the NMF solution of methyl ammonium bromide, and obvious stratification can be observed. After stirring the solution, it can be observed that the quantum dots are transferred to the NMF solution. After stirring for five minutes, it can be observed that all the quantum dots are transferred to the lower layer of NMF solution, indicating that the quantum dot ligand exchange is complete, that is, the OA ligands on the surface of the CdTe quantum dots are exchanged with the methyl ammonium bromide in the NMF solution.

[0038] S9: Preparation of quantum dot intermediate-band solar cells based on type II band structure.

[0039] Take out the plasma-cleaned FTO conductive substrate, add 50 μL of TiO2 dense layer precursor solution, spin-coat at 4000 rpm for 30 seconds, and then anneal at 150°C for 10 minutes to obtain a TiO2 dense layer. After the substrate cools to room temperature, add 30 μL of TiO2 mesoporous layer precursor solution, spin-coat at 5000 rpm for 30 seconds, and anneal at 500°C in a muffle furnace for 30 minutes to obtain a TiO2 mesoporous layer. The preparation method of the light absorption layer is described below.

[0040] Take the solution after ligand exchange described in step S8, add n-hexane and stir for 5 minutes to wash the solution; repeat the washing 3 times. After washing, take out the NMF dispersion of quantum dots, add 4 mL of anhydrous ethanol, centrifuge at 8000 rpm for 3 minutes, and redisperse it in 200 μL of NMF solution after centrifugation. Mix the above-mentioned quantum dot dispersion with 600 μL of MAPbBr3 perovskite precursor solution and stir for 15 minutes to obtain a light absorption layer precursor solution. The doping concentration of quantum dots in the light absorption layer precursor solution corresponding to this embodiment is 10% (concentration is calculated by molar mass). Take 60 μL of the light absorption layer precursor solution, spin coat it at 800 rpm for 10 seconds, then spin coat it at 4000 rpm for 60 seconds, and anneal it at 100 ° C for 10 minutes after spin coating to obtain a light absorption layer.

[0041] After the substrate cools to room temperature, a layer of carbon electrode is scraped on the surface of the deposited light absorption layer to serve as the positive electrode of the battery. The preparation process of the negative electrode of the battery can be prepared according to the existing method, which will not be described in detail here.

[0042] Figure 3 (a) and (b) are respectively the energy band structures of CdTe and MAPbBr3 in the light absorption layer of the intermediate band solar cell prepared by the present invention and the working principle of the intermediate band. Figure 3It can be seen that the band gap of the perovskite material MAPbBr3 is 2.3eV. By introducing CdTe quantum dots, an intermediate band is inserted into its band gap, and two-step photon absorption (TPSA) is obtained, providing a new transfer path for photogenerated carriers.

[0043] Figure 4 is the SEM image of the sample prepared in this embodiment, Figure 4 It can be clearly seen that the FTO conductive substrate, the TiO2 dense layer, the TiO2 mesoporous layer on the TiO2 dense layer, and CdTe and MAPbBr3 distributed in the same layer. Figure 4 The carbon electrode is not shown in the figure because the thickness of the carbon electrode is 20 μm. If the carbon electrode is fully displayed, the film layer under the carbon electrode will not be clearly displayed.

[0044] Example 2 Compared with Example 1, in step S8 of this embodiment, 0.224 mg of methyl ammonium bromide was taken and dissolved in 4 mL of NMF solution; 2 mL of n-hexane dispersion of CdTe-OA quantum dots was taken and diluted with 2 mL of n-hexane. The other steps were the same as those in Example 1.

[0045] The doping concentration of the quantum dots in the light absorption layer precursor solution in this embodiment is 20% (the concentration is calculated by molar mass).

[0046] Example 3 Compared with Example 1, in step S8 of this embodiment, 0.336 mg of methyl ammonium bromide was taken and dissolved in 4 mL of NMF solution; 3 mL of n-hexane dispersion of CdTe-OA quantum dots was taken and diluted with 1 mL of n-hexane. The other steps were the same as those in Example 1.

[0047] The doping concentration of the quantum dots in the light absorption layer precursor solution in this embodiment is 30% (the concentration is calculated by molar mass).

[0048] Comparative Example 1 The preparation of the MAPbBr3 perovskite solar cell without quantum dot doping is prepared in this comparative example. The preparation method is different from that in Example 1 except for the preparation of the light absorption layer. The preparation processes of the TiO2 dense layer precursor solution, the TiO2 mesoporous layer precursor solution and the MAPbBr3 perovskite precursor solution are the same as those in Example 1 and will not be repeated here. The preparation method of the MAPbBr3 perovskite solar cell without quantum dot doping in this comparative example is as follows: Take out the plasma-cleaned FTO conductive substrate, add 50μL of TiO2 dense layer precursor solution, spin-coat at 4000rpm for 30s, and then anneal at 150℃ for 10min to obtain a TiO2 dense layer. After the substrate cools to room temperature, add 30μL of TiO2 mesoporous layer precursor solution, spin-coat at 5000rpm for 30s, and anneal at 500℃ in a muffle furnace for 30min to obtain a TiO2 mesoporous layer. After the substrate cools to room temperature, add 60μL of MAPbBr3 perovskite precursor solution, spin-coat at 800rpm for 10s, then spin-coat at 4000rpm for 60s, and anneal at 100℃ for 10min after spin coating to obtain a light absorption layer. After the substrate cools to room temperature, scrape a layer of carbon electrode on the surface of the deposited light absorption layer as the positive electrode of the battery.

[0049] In order to test the light absorbing layers in Examples 1 to 3 and Comparative Example 1, the light absorbing layers in Examples 1 to 3 and Comparative Example 1 were prepared on FTO conductive substrates, and then the absorption spectra of the corresponding light absorbing layers were tested. The results are as follows: Figure 5 shown. Figure 5 The absorption spectrum shows sub-bandgap photon absorption; the light absorption of the light absorption layer is higher than that of ordinary MAPbBr3 in the red light band and near-infrared band, and the absorption increases with the increase of the doping ratio.

[0050] The external quantum efficiency (EQE) of the intermediate zone solar cells prepared in Examples 1 to 3 and the MAPbBr3 perovskite solar cell prepared in Comparative Example 1 was tested. The results are as follows: Figure 6 As shown. Figure 6 It can be seen that the intermediate-band solar cell has a photoelectric response in the red and near-infrared bands that ordinary MAPbBr3 solar cells do not have, and the current increases with the increase of the doping ratio.

[0051] Figure 7 This is an IT curve spectrum of the photoelectric response of the intermediate zone solar cell prepared in Example 2 when excited by an 830nm laser. As can be seen from the figure, there is no photocurrent decay as time increases.

[0052] Figure 8 This is an IT curve spectrum of the photoelectric response of the intermediate zone solar cell prepared in Example 2 when excited by a 1550nm laser. As can be seen from the figure, there is no photocurrent decay as time increases.

[0053] Figure 6~Figure 8 All of them show that sub-bandgap photons can be converted into electric current, indicating that the present invention has successfully prepared intermediate-band solar cells.

[0054] In the embodiment of the present invention, an experiment was also conducted with a doping concentration of 40% for CdTe quantum dots in the light absorption layer precursor solution. The performance results at a doping concentration of 40% were equivalent to those at a doping concentration of 30%. It is speculated that this is because: as the doping concentration of CdTe quantum dots increases, they cannot be effectively dispersed in the perovskite material MAPbBr3, so that blindly increasing the doping amount cannot infinitely improve the performance of the sample.

Claims

1. A quantum dot intermediate band solar cell based on type II energy band structure, characterized in that: Its structure includes: an FTO conductive substrate; a TiO2 dense layer formed on the FTO conductive substrate; a TiO2 mesoporous layer formed on the TiO2 dense layer; a light absorption layer formed in the TiO2 mesoporous layer; and a carbon electrode formed on the light absorption layer; the light absorption layer is prepared by spin coating a light absorption layer precursor liquid formed by CdTe quantum dots and MAPbBr3 perovskite, and the CdTe quantum dots are obtained by first forming organic long-chain ligands on the surface of the quantum dots and then replacing the organic long-chain ligands with short-chain ligands.

2. The quantum dot intermediate band solar cell based on type II energy band structure according to claim 1 is characterized in that: The molar mass concentration of CdTe quantum dots in the light absorption layer precursor solution is 10%~30%.

3. The quantum dot intermediate band solar cell based on type II energy band structure according to claim 1 is characterized in that: The organic long-chain ligand is oleic acid, stearic acid, octadecylphosphonic acid, tetradecylphosphonic acid, oleylamine, octylamine or tributylphosphine; the short-chain ligand is methylammonium bromide, lead bromide, methylamine lead bromide, methylammonium iodide, lead iodide, methylamine lead iodide, sodium sulfide, sodium chloride or ammonium chloride.

4. A method for preparing a quantum dot intermediate band solar cell based on a type II energy band structure, characterized in that: The steps include: S1, dissolving tellurium powder in tributylphosphine, heating under nitrogen environment, and then adding octadecene to obtain Te-TBP precursor solution; S2, mixing cadmium oxide, an organic compound and octadecene, passing nitrogen gas and heating; and then adding the Te-TBP precursor solution in step S1 to the heated solution; S3, mixing the solution obtained in step S2 with acetone, centrifuging, drying, and then dispersing in n-hexane to obtain a n-hexane dispersion of CdTe quantum dots; the obtained CdTe quantum dots form organic long-chain ligands on their surfaces; S4, preparing a TiO2 mesoporous layer precursor solution: mixing titanium dioxide slurry with anhydrous ethanol, and stirring to prepare a TiO2 mesoporous layer precursor solution; S5. Prepare MAPbBr3 perovskite precursor solution: mix methyl ammonium bromide and lead bromide, add to N-methylformamide solution, and stir overnight to obtain MAPbBr3 perovskite precursor solution; S6. Prepare a TiO2 dense layer precursor solution: mix isopropyl titanate with anhydrous ethanol, and mix hydrochloric acid with anhydrous ethanol; in a glove box under a nitrogen environment, slowly drop the anhydrous ethanol solution containing hydrochloric acid into the anhydrous ethanol solution of isopropyl titanate using a pipette, stir, and then filter to obtain a TiO2 dense layer precursor solution; S7, cleaning of the FTO conductive substrate: soak the FTO conductive substrate in toluene, acetone, anhydrous ethanol, and deionized water in turn and perform ultrasonic cleaning respectively, blow dry with a nitrogen gun after cleaning, and then use a plasma cleaning machine to clean the surface of the FTO conductive substrate; S8, quantum dot ligand exchange: dissolving the short-chain ligand in N-methylformamide, taking the n-hexane dispersion of CdTe quantum dots obtained in step S3, and adding n-hexane to dilute; adding the diluted CdTe n-hexane dispersion to the N-methylformamide solution of the short-chain ligand, stirring, so that the organic long-chain ligand on the surface of the CdTe quantum dots is replaced by the short-chain ligand, thereby realizing ligand exchange; S9, preparation of a TiO2 dense layer: spin-coating the TiO2 dense layer precursor solution in step S6 on the FTO conductive substrate cleaned in step S7 to prepare a TiO2 dense layer; S10, preparation of TiO2 mesoporous layer: spin coating the TiO2 mesoporous layer precursor solution obtained in step S4 on the TiO2 dense layer obtained in step S9 to obtain a TiO2 mesoporous layer; S11, preparation of light absorption layer precursor solution: adding n-hexane to the ligand exchange solution obtained in step S8 for washing, taking out the N-methylformamide dispersion of quantum dots after washing, adding anhydrous ethanol for centrifugation, and redispersing it in N-methylformamide solution after centrifugation; mixing the redispersed N-methylformamide dispersion of quantum dots with the MAPbBr3 perovskite precursor solution in step S5, stirring, and obtaining a light absorption layer precursor solution; S12, preparation of a light absorbing layer: spin coating the light absorbing layer precursor solution obtained in step S11 on the TiO2 mesoporous layer obtained in step S10, and the light absorbing layer precursor solution is filled in the mesopores of the TiO2 mesoporous layer to form a light absorbing layer; S13. Preparation of carbon electrode: A carbon electrode is prepared by scraping on the light absorbing layer obtained in step S12.

5. The method for preparing a quantum dot intermediate band solar cell based on a type II energy band structure according to claim 4, characterized in that: The molar mass concentration of CdTe quantum dots in the light absorption layer precursor solution obtained in step S11 is 10% to 30%.

6. The method for preparing a quantum dot intermediate band solar cell based on a type II energy band structure according to claim 4, characterized in that: The organic long-chain ligand is oleic acid, stearic acid, octadecylphosphonic acid, tetradecylphosphonic acid, oleylamine, octylamine or tributylphosphine; the short-chain ligand is methylammonium bromide, lead bromide, methylamine lead bromide, methylammonium iodide, lead iodide, methylamine lead iodide, sodium sulfide, sodium chloride or ammonium chloride.

7. The method for preparing a quantum dot intermediate band solar cell based on a type II energy band structure according to claim 4, characterized in that: The process conditions for preparing the light absorbing layer in step S12 are: spin coating at 800 rpm for 10 seconds, then spin coating at 4000 rpm for 60 seconds, and annealing at 100° C. for 10 minutes after spin coating to obtain the light absorbing layer.

Citation Information

Patent Citations

  • Solar cell with double photoelectric conversion function

    CN109830605A

  • Composite light absorption layer solar cell and preparation method thereof

    CN111106192A

  • Light absorbing layer, photoelectric transducer, and solar cell

    CN112088442A

  • Preparation method of broadband spectrum absorption mesoporous quantum dot parallel laminated solar cell

    CN113921725A

  • Perovskite quantum dot solar cell and preparation method thereof

    CN113937220A